Heavy filling material as well as preparation method and application thereof

By combining modified iron tailings with fly ash, wollastonite and fiber, combined with calcining technology of sodium exciters and calcium exciters, the particle size and additives are optimized, and the problems of low density, poor fluidity and poor water resistance of the filling material are solved. A filling material with high density, high compressive strength and good water resistance is achieved, improving coal quality and economic benefits.

CN119430780AActive Publication Date: 2025-02-14XUCHEN MINING TECH DEV (XUZHOU) CO LTD

Patent Information

Application Number
CN202411589932.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-02-14
Estimated Expiration
2044-11-08

AI Technical Summary

Technical Problem

The existing coal mine filling materials have low density, poor liquidity and poor water resistance, which affect the quality of coal and economic benefits.

Method used

By modifying the combination of iron tailings with fly ash, wollastonite and fiber, the combination of sodium exciter and calcium exciter is used for calcination, optimize the particle size combination and add a quick-setting agent, suspending agent and water reducing agent to improve the filler body density, compressive strength and water resistance.

Benefits of technology

It significantly improves the density, compressive strength and water resistance of the filling body, is suitable for coal mine filling applications, and improves coal quality and economic benefits.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to a heavy filling material for coal mines and a preparation method thereof.The heavy filling material comprises modified iron tailings, fly ash, wollastonite, fibers and the like, the activity of calcined iron tailings is effectively improved by using a composite modification system of a calcium activator and a sodium activator, rich C-S-H gel and C-A-S-H gel are promoted to be formed, and the filling effect is improved. The modified iron tailings with different particle sizes are mixed for use, the particle size combination of the filling material is optimized, and then the compressive strength, density and water resistance of a filling body are remarkably improved; the fly ash, the wollastonite and the fibers are matched, so that the compactness, the compressive strength and the water resistance of the filling body are further improved. The synergistic effect of the fibers, the wollastonite and the fly ash is beneficial to improving the comprehensive performance of the filling body, and the filling body is particularly suitable for being applied to coal mine filling.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of coal mine production safety, and specifically relates to a heavy filling material and a preparation method and application thereof. Background Art

[0002] Underground coal mining often causes a series of serious problems, such as rock fracture, surface subsidence, groundwater damage and environmental pollution. These challenges make scientific coal mining extremely difficult. As an environmentally friendly mining technology, backfill mining technology plays an important role in scientific coal mining. As a key branch of coal mine backfill mining technology, cementing backfilling fills the goaf with cementing materials to support the surrounding rock formations, reduces the impact of mining activities on the overlying rock formations, improves resource recovery, and reduces the discharge of surface waste, thereby reducing environmental pollution. This technology has been widely used in coal mines at home and abroad. The core of cementing backfilling mining technology lies in the selection of backfilling materials, because the performance of the materials directly affects the implementation effect of the backfilling mining process and the effectiveness of rock formation control. Usually, coal mine cementing backfilling materials are made by mixing solid wastes such as tailings and fly ash with binders and stirring with water. In typical cementing backfilling materials, the content of binders is approximately between 15% and 40%, and the mass concentration of slurry is between 60% and 85%.

[0003] In the filling operation of the damaged area of ​​the coal mine, high water filling material is widely used because of its easy construction. However, the density of this material is usually 1.11-1.16g / cm 3 , compared to the density of coal and gangue 1.4g / cm 3 This density difference makes it difficult to effectively wash the area filled with high-water materials or the area bordering it with heavy medium coal preparation, which in turn affects the coal quality and reduces the economic benefits of coal. Summary of the invention

[0004] In view of the technical problems existing in the above-mentioned prior art, the purpose of the present invention is to provide a heavy filling material and its preparation method and application, so as to solve the problems of low density, poor fluidity and poor water resistance of the filling material in the prior art. The filling material significantly improves the density, compressive strength and water resistance of the filling body by modifying iron tailings, combining fly ash, wollastonite and fiber, and is particularly suitable for application in coal mine filling.

[0005] The present invention provides a heavy filling material, which comprises the following components in parts by weight: 40-80 parts of modified iron tailings, 10-30 parts of fly ash, 10-20 parts of wollastonite, 5-10 parts of fiber, 1-8 parts of accelerating setting agent, 1-8 parts of suspending agent, 1-3 parts of water reducing agent and 120-300 parts of water.

[0006] The preparation method of modified iron tailings comprises the following steps:

[0007] S1. 100 parts by weight of the iron tailings are crushed and dried, and mixed evenly with 10-15 parts by weight of an activator, wherein the activator comprises a sodium activator and a calcium activator, wherein the sodium activator comprises at least one of sodium chloride, sodium sulfate and sodium hydroxide; the calcium activator comprises at least one of calcium hydroxide, calcium oxide, calcium chloride and gypsum, and the mass ratio of the sodium activator to the calcium activator is 1-3:5-10;

[0008] S2. The mixed material in step S1 is transported to a rotary kiln for calcination, cooling, grinding, and respectively passed through 10 mm and 5 mm sieves to obtain a fine particle size of d1 < 5 mm and a coarse particle size of 5 ≤ d2 < 10 mm. The fine particle size and the coarse particle size are mixed uniformly in a mass ratio of 1-3:5-8 to obtain a modified iron tailings.

[0009] The fibers include at least one of glass fibers, polypropylene fibers, polyester fibers, and basalt fibers, and the length of the fibers is 2-10 mm; more preferably, the length of the fibers is 4-8 microns.

[0010] The water reducer includes at least one of a naphthalene-based water reducer, a melamine-based water reducer or a polycarboxylic acid-based water reducer.

[0011] The accelerating setting agent includes at least one of sodium aluminate, sodium sulfate or sodium carbonate.

[0012] The suspending agent includes at least one of sodium carboxymethylcellulose, water-soluble polyvinyl alcohol or hydroxypropyl methylcellulose.

[0013] In the step S2, the calcination temperature is 800-1400° C., and the calcination time is 2-5 hours.

[0014] The present invention also provides a method for heavy filling materials, comprising the following steps:

[0015] 1) Accurately weigh 40-80 parts of modified iron tailings, 10-30 parts of fly ash, 10-20 parts of wollastonite, 5-10 parts of fiber, 1-8 parts of accelerating setting agent, 1-8 parts of suspending agent, and 120-300 parts of water;

[0016] 2) First, evenly mix the modified iron tailings, fly ash, wollastonite, fiber, accelerating setting agent and suspending agent, and then evenly mix with water to make a heavy filling material.

[0017] There is no specific requirement for the mixing temperature and time in step 2), as long as the materials are mixed evenly. Furthermore, preferably, the mixing temperature is 20-40° C. and the mixing time is 20-60 min.

[0018] The present invention also relates to an application of a heavy filling material in coal mine filling, characterized in that the filling material is mixed and then pumped to a use site.

[0019] The present invention adopts a combination of sodium activator and calcium activator, which can effectively improve the activity of calcined iron tailings, optimize its microstructure, and enhance durability. The use of this composite activator can accelerate the dissolution process of silicate in the iron tailings, promote the formation of abundant hydration products, such as CSH gel and CASH gel, and thus significantly improve the strength of the material. In addition, the generated hydration products, especially CSH gel, further enhance the durability and density of the material due to its excellent compactness and anti-penetration performance.

[0020] The present invention adopts a mixture of modified iron tailings of different particle sizes, optimizes the particle size combination of the filling material, effectively improves its rheological properties, and thus enhances the stability and fluidity of the filling body. In this method, the coarse-grained modified iron tailings construct a solid skeleton, providing the necessary support for the filling body; the fine-grained iron tailings penetrate and fill the gaps between the coarse particles, further improving the compactness of the filling body. This scientific ratio of coarse and fine particles promotes the uniform distribution of stress in the filling body, effectively avoids the problem of stress concentration, and enhances the overall stability of the filling body. At the same time, the filling effect of the fine-grained iron tailings also increases the density of the filling body, ensuring the long-term stability and safety of the project. Through this innovative particle size matching strategy, the present invention significantly improves the performance of the filling material and provides strong technical support for the sustainable development of coal mines.

[0021] The second concept of the present invention is that the combination of modified iron tailings and fibers can effectively improve the mechanical properties and stability of the filling body. The modified iron tailings play a cementing role in the filling body, forming hydration products such as calcium silicate hydrate (CSH) gel, which enhances the early strength of the filling body. The addition of fibers further strengthens the structure of the filling body. The fibers form a network structure in the filling body, improving its crack resistance and ductility. The reinforcing effect of this structure reduces the defects inside the filling body and optimizes the internal pore structure, thereby improving the compressive strength of the filling body. At the same time, the addition of fibers can also improve the rheological properties of the filling material, enhance its fluidity and stability, which is of great significance for improving the filling efficiency and reducing losses during the filling process.

[0022] Furthermore, appropriately increasing the fiber length can increase the contact area between the fiber and the filling matrix, enhance the cohesion and structural stability, and thus improve the strength and density of the filling; however, too long a fiber length may reduce the fluidity of the slurry, increase the viscosity and yield stress, and affect the uniformity and density of the filling. The fiber length is 2-10 mm; more preferably, the fiber length is 4-8 microns.

[0023] The present invention utilizes the high density of wollastonite, which has a density value between 2.75-2.91 g / cm 3 This high-density characteristic helps to improve the stability and density of the filling, thereby enhancing the density and compressive strength of the filling.

[0024] Compared with the prior art, the present invention has achieved the following beneficial effects:

[0025] 1) The present invention mainly uses iron tailings, fly ash, etc. to prepare filling materials, avoiding solid waste pollution of the environment and greatly reducing the cost of filling material preparation; the combination of sodium activator and calcium activator can effectively improve the activity of calcined iron tailings, and further enhance the strength and density of the filling body. Modified iron tailings of different particle sizes are mixed and used, and the coarse-grained modified iron tailings build a solid skeleton, providing necessary support for the filling body; the fine-grained iron tailings penetrate and fill the gaps between the coarse particles, further improving the density, strength and water resistance of the filling body.

[0026] 2) The present invention significantly improves the mechanical properties and stability of the filling body by combining modified iron tailings with fibers. The modified iron tailings play a cementing role in the filling body, and enhances the early strength of the filling body by forming hydration products such as hydrated calcium silicate (CSH) gel. At the same time, the fibers construct a network structure in the filling body, further improving the strength of the filling body. In addition, the use of wollastonite with a higher density as a filling material further enhances the density and compressive strength of the filling body. Due to its volcanic ash activity, fly ash can generate more hydration products, such as CSH gel, thereby further improving the density, compressive strength and water resistance of the filling body. Overall, the synergistic effect of modified iron tailings, fibers, wollastonite and fly ash jointly improves the comprehensive performance of the filling body.

[0027] 3) The raw materials such as iron tailings, fly ash, wollastonite, etc. used in the present invention are not only widely available, but also low in cost. At the construction site, only simple mixing and stirring is required to quickly prepare the required filling materials. This method greatly simplifies the on-site operation process, significantly reduces production costs, and greatly improves construction efficiency. DETAILED DESCRIPTION

[0028] The technical solution of the present invention is further described below in combination with and through specific implementation methods. However, the following examples are only simplified examples of the present invention and do not represent or limit the scope of protection of the present invention. The scope of protection of the present invention shall be subject to the claims.

[0029] Experimental Materials:

[0030] The iron tailings used in the present invention are derived from tailings produced by an iron ore concentrator, and the main chemical components are silicon oxide, iron oxide, aluminum oxide, magnesium oxide and calcium oxide, and the specific composition is: SiO2 62.11%, CaO 3.11%, MgO 4.34%, Al2O3 13.81%, Fe2O3 11.26%, K2O 2.33%, Na2O 0.64%, and others 2.40%.

[0031] The average particle size of wollastonite is 30-50 μm, the average particle size of fly ash is 20-40 μm, and other raw materials are commercially available.

[0032] Example 1

[0033] The present embodiment provides a heavy filling material, the formula of which is: 40 parts of modified iron tailings, 30 parts of fly ash, 20 parts of wollastonite, 8 parts of fiber, 4 parts of accelerating setting agent, 5 parts of suspending agent, 2 parts of water reducing agent, and 150 parts of water.

[0034] The preparation method of modified iron tailings comprises the following steps:

[0035] S1. 100 parts by weight of the iron tailings are crushed and dried, and mixed evenly with 10 parts by weight of an activator, wherein the activator comprises a sodium activator and a calcium activator, wherein the sodium activator comprises sodium chloride, the calcium activator comprises calcium hydroxide, and the mass ratio of the sodium activator to the calcium activator is 1:5;

[0036] S2. The mixed material in step S1 is conveyed to a rotary kiln, calcined at 800°C for 5h, cooled, ground, and passed through 10mm and 5mm sieves respectively to obtain a fine particle size of d1<5mm and a coarse particle size of 5≤d2<10mm. The fine particle size and the coarse particle size are uniformly mixed in a mass ratio of 1:5 to obtain a modified iron tailings.

[0037] The fiber is glass fiber, and the length of the fiber is 6 mm.

[0038] The water reducer is a naphthalene-based water reducer.

[0039] The accelerating setting agent is sodium aluminate.

[0040] The suspending agent is sodium carboxymethyl cellulose.

[0041] This embodiment also provides a method for preparing a heavy filling material, comprising the following steps:

[0042] 1) Accurately weigh 40 parts of modified iron tailings, 30 parts of fly ash, 20 parts of wollastonite, 8 parts of fiber, 4 parts of accelerating setting agent, 5 parts of suspending agent, 2 parts of water reducing agent, and 150 parts of water;

[0043] 2) First, evenly mix the modified iron tailings, fly ash, wollastonite, fiber, accelerating setting agent and suspending agent, and then evenly mix with water to make a heavy filling material.

[0044] Example 2

[0045] The present embodiment provides a heavy filling material, the formula of which is: 60 parts of modified iron tailings, 15 parts of fly ash, 20 parts of wollastonite, 10 parts of fiber, 5 parts of accelerating setting agent, 4 parts of suspending agent, 3 parts of water reducing agent, and 200 parts of water.

[0046] The preparation method of modified iron tailings comprises the following steps:

[0047] S1. 100 parts by weight of the iron tailings are crushed and dried, and mixed evenly with 15 parts by weight of an activator, wherein the activator comprises a sodium activator and a calcium activator, wherein the sodium activator comprises sodium sulfate; the calcium activator comprises gypsum, and the mass ratio of the sodium activator to the calcium activator is 2:7;

[0048] S2. The mixed material in step S1 is conveyed to a rotary kiln, calcined at 1000°C for 3h, cooled, ground, and passed through 10mm and 5mm sieves respectively to obtain a fine particle size of d1<5mm and a coarse particle size of 5≤d2<10mm. The fine particle size and the coarse particle size are uniformly mixed in a mass ratio of 3:8 to obtain a modified iron tailings.

[0049] The fiber is basalt fiber, and the length of the fiber is 10 mm.

[0050] The water reducing agent is a melamine water reducing agent.

[0051] The accelerating agent is sodium carbonate.

[0052] The suspending agent is water-soluble polyvinyl alcohol.

[0053] This embodiment also provides a method for preparing a heavy filling material, comprising the following steps:

[0054] 1) Accurately weigh 60 parts of modified iron tailings, 15 parts of fly ash, 20 parts of wollastonite, 10 parts of fiber, 5 parts of accelerating setting agent, 4 parts of suspending agent, 3 parts of water reducing agent, and 200 parts of water;

[0055] 2) First, evenly mix the modified iron tailings, fly ash, wollastonite, fiber, accelerating setting agent and suspending agent, and then evenly mix with water to make a heavy filling material.

[0056] Example 3

[0057] The present embodiment provides a heavy filling material, the formula of which is: 70 parts of modified iron tailings, 10 parts of fly ash, 10 parts of wollastonite, 10 parts of fiber, 2 parts of accelerating setting agent, 3 parts of suspending agent, 3 parts of water reducing agent, and 180 parts of water.

[0058] The preparation method of modified iron tailings comprises the following steps:

[0059] S1. 100 parts by weight of the iron tailings are crushed and dried, and mixed evenly with 12 parts by weight of an activator, wherein the activator comprises a sodium activator and a calcium activator, wherein the sodium activator comprises sodium chloride and sodium sulfate in a 1:1 combination; the calcium activator is calcium oxide, and the mass ratio of the sodium activator to the calcium activator is 3:10;

[0060] S2. The mixed material in step S1 is conveyed to a rotary kiln, calcined at 1100°C for 3h, cooled, ground, and passed through 10mm and 5mm sieves respectively to obtain a fine particle size of d1<5mm and a coarse particle size of 5≤d2<10mm. The fine particle size and the coarse particle size are uniformly mixed in a mass ratio of 3:5 to obtain a modified iron tailings.

[0061] The fiber is polypropylene fiber, and the length of the fiber is 8 mm.

[0062] The water reducing agent is a melamine water reducing agent.

[0063] The accelerating setting agent is sodium sulfate.

[0064] The suspending agent is hydroxypropyl methylcellulose.

[0065] This embodiment also provides a method for preparing a heavy filling material, comprising the following steps:

[0066] 1) Accurately weigh 70 parts of modified iron tailings, 10 parts of fly ash, 10 parts of wollastonite, 10 parts of fiber, 2 parts of accelerating setting agent, 3 parts of suspending agent, 3 parts of water reducing agent, and 180 parts of water;

[0067] 2) First, evenly mix the modified iron tailings, fly ash, wollastonite, fiber, accelerating setting agent and suspending agent, and then evenly mix with water to make a heavy filling material.

[0068] Example 4

[0069] The present embodiment provides a heavy filling material, the formula of which is: 80 parts of modified iron tailings, 15 parts of fly ash, 20 parts of wollastonite, 6 parts of fiber, 1 part of accelerating setting agent, 3 parts of suspending agent, 3 parts of water reducing agent, and 230 parts of water.

[0070] The preparation method of modified iron tailings comprises the following steps:

[0071] S1. 100 parts by weight of the iron tailings are crushed and dried, and mixed with 10 parts by weight of an activator, wherein the activator comprises a sodium activator and a calcium activator, wherein the sodium activator is sodium sulfate and sodium hydroxide in a ratio of 1:2; the calcium activator comprises calcium chloride and gypsum in a ratio of 2:1, and the mass ratio of the sodium activator to the calcium activator is 1:6;

[0072] S2. The mixed material in step S1 is conveyed to a rotary kiln, calcined at 1200°C for 2.5h, cooled, ground, and passed through 10mm and 5mm sieves respectively to obtain a fine particle size of d1<5mm and a coarse particle size of 5≤d2<10mm. The fine particle size and the coarse particle size are uniformly mixed in a mass ratio of 2:7 to obtain a modified iron tailings.

[0073] The fiber is glass fiber, and the length of the fiber is 10 mm.

[0074] The water reducer is a naphthalene-based water reducer.

[0075] The accelerating agent is sodium carbonate.

[0076] The suspending agent is hydroxypropyl methylcellulose.

[0077] This embodiment also provides a method for preparing a heavy filling material, comprising the following steps:

[0078] 1) Accurately weigh 80 parts of modified iron tailings, 15 parts of fly ash, 20 parts of wollastonite, 6 parts of fiber, 1 part of accelerating setting agent, 3 parts of suspending agent, 3 parts of water reducing agent, and 230 parts of water;

[0079] 2) First, evenly mix the modified iron tailings, fly ash, wollastonite, fiber, accelerating setting agent and suspending agent, and then evenly mix with water to make a heavy filling material.

[0080] Example 5

[0081] The present embodiment provides a heavy filling material, the formula of which is: 65 parts of modified iron tailings, 25 parts of fly ash, 20 parts of wollastonite, 7 parts of fiber, 3 parts of accelerating setting agent, 6 parts of suspending agent, 3 parts of water reducing agent, and 250 parts of water.

[0082] The preparation method of modified iron tailings comprises the following steps:

[0083] S1. 100 parts by weight of the iron tailings are crushed and dried, and mixed with 15 parts by weight of an activator, wherein the activator comprises a sodium activator and a calcium activator, wherein the sodium activator is sodium hydroxide; the calcium activator is calcium hydroxide, and the mass ratio of the sodium activator to the calcium activator is 2:5;

[0084] S2. The material mixed evenly in step S1 is conveyed to a rotary kiln, calcined at 1300°C for 3h, cooled, ground, and passed through 10mm and 5mm sieves respectively to obtain a fine particle size of d1<5mm and a coarse particle size of 5≤d2<10mm. The fine particle size and the coarse particle size are mixed evenly in a mass ratio of 1:8 to obtain a modified iron tailings.

[0085] The fibers are a combination of polypropylene fibers and polyester fibers in a ratio of 1:1, and the length of the fibers is 2 mm.

[0086] The water reducing agent is a melamine water reducing agent.

[0087] The accelerating agent is sodium carbonate.

[0088] The suspending agent is sodium carboxymethyl cellulose.

[0089] This embodiment provides a method for preparing a heavy filling material, comprising the following steps:

[0090] 1) Accurately weigh 65 parts of modified iron tailings, 25 parts of fly ash, 20 parts of wollastonite, 7 parts of fiber, 3 parts of accelerating setting agent, 6 parts of suspending agent, 3 parts of water reducing agent, and 250 parts of water;

[0091] 2) First, evenly mix the modified iron tailings, fly ash, wollastonite, fiber, accelerating setting agent and suspending agent, and then evenly mix with water to make a heavy filling material.

[0092] Example 6

[0093] The present embodiment provides a heavy filling material, the formula of which is: 75 parts of modified iron tailings, 25 parts of fly ash, 15 parts of wollastonite, 8 parts of fiber, 3 parts of accelerating setting agent, 3 parts of suspending agent, 2 parts of water reducing agent, and 280 parts of water.

[0094] The preparation method of modified iron tailings comprises the following steps:

[0095] S1. 100 parts by weight of the iron tailings are crushed and dried, and mixed evenly with 13 parts by weight of an activator, wherein the activator comprises a sodium activator and a calcium activator, wherein the sodium activator is sodium sulfate; the calcium activator is calcium oxide, and the mass ratio of the sodium activator to the calcium activator is 1:8;

[0096] S2. The mixed material in step S1 is conveyed to a rotary kiln, calcined at 1100°C for 3h, cooled, ground, and passed through 10mm and 5mm sieves respectively to obtain a fine particle size of d1<5mm and a coarse particle size of 5≤d2<10mm. The fine particle size and the coarse particle size are uniformly mixed in a mass ratio of 2:7 to obtain a modified iron tailings.

[0097] The fibers are polyester fibers and basalt fibers in a ratio of 1:3, and the length of the fibers is 4 mm.

[0098] The water reducing agent is a polycarboxylic acid water reducing agent.

[0099] The accelerating setting agent is sodium aluminate.

[0100] The suspending agent is water-soluble polyvinyl alcohol.

[0101] This embodiment also provides a method for preparing a heavy filling material, comprising the following steps:

[0102] 1) Accurately weigh 75 parts of modified iron tailings, 25 parts of fly ash, 15 parts of wollastonite, 8 parts of fiber, 3 parts of accelerating agent, 3 parts of suspending agent, 2 parts of water reducing agent, and 280 parts of water;

[0103] 2) First, evenly mix the modified iron tailings, fly ash, wollastonite, fiber, accelerating setting agent and suspending agent, and then evenly mix with water to make a heavy filling material.

[0104] Example 7

[0105] The length of the glass fiber is 2 mm, and other conditions are the same as those in Example 1.

[0106] Example 8

[0107] The length of the glass fiber is 4 mm, and other conditions are the same as those in Example 1.

[0108] Example 9

[0109] The length of the glass fiber is 8 mm, and other conditions are the same as those in Example 1.

[0110] Example 10

[0111] The length of the glass fiber is 10 mm, and other conditions are the same as those in Example 1.

[0112] Comparative Example 1

[0113] The difference from Example 1 is that the preparation method of the modified iron tailings is as follows:

[0114] S1. 100 parts by weight of iron tailings are crushed and dried;

[0115] S2. The dried material in step S1 is conveyed to a rotary kiln, calcined at 800°C for 5h, cooled, ground, and passed through 10mm and 5mm sieves respectively to obtain a fine particle size of d1<5mm and a coarse particle size of 5≤d2<10mm. The fine particle size and the coarse particle size are uniformly mixed in a mass ratio of 1:5 to obtain a modified iron tailings.

[0116] Comparative Example 2

[0117] The difference from Example 1 is that in the preparation process of the modified iron tailings, an equal amount of sodium chloride is used instead of calcium hydroxide, and the rest is the same as Example 1.

[0118] Comparative Example 3

[0119] The difference from Example 1 is that in the preparation process of the modified iron tailings, an equal amount of calcium hydroxide is used instead of sodium chloride, and the rest is the same as Example 1.

[0120] Comparative Example 4

[0121] The difference from Example 1 is that an equal amount of fine-particle-size modified iron tailings is used instead of coarse-particle-size ones, that is, all fine-particle-size modified iron tailings are used, and the rest is the same as Example 1.

[0122] Comparative Example 5

[0123] The difference from Example 1 is that an equal amount of coarse-particle-sized modified iron tailings is used instead of fine-particle-sized ones, that is, all coarse-particle-sized modified iron tailings are used, and the rest is the same as Example 1.

[0124] Comparative Example 6

[0125] The difference from Example 1 is that the weight ratio of the fine particle size (d1) to the coarse particle size (d2) is 1:10, and the rest is the same as Example 1.

[0126] Comparative Example 7

[0127] The difference from Example 1 is that the weight ratio of the fine particle size (d1) to the coarse particle size (d2) is 4:1, and the rest is the same as Example 1.

[0128] Comparative Example 8

[0129] The difference from Example 1 is that an equal amount of modified iron tailings is used instead of fly ash.

[0130] Comparative Example 9

[0131] The difference from Example 1 is that an equal amount of modified iron tailings is used instead of wollastonite.

[0132] Comparative Example 10

[0133] The difference from Example 1 is that an equal amount of modified iron tailings is used instead of fibers.

[0134] The slump, water seepage rate, strength, density and water resistance retention rate of the filling materials in the embodiments and comparative examples were tested. The performance of the high-quality filling materials is shown in Table 1.

[0135] Retention rate of compressive strength against water penetration: Take samples from the underground filling area of ​​the coal mine at an age of 48 days to test the compressive strength, recorded as M1. Then soak the specimens in water for 2 days, and test the compressive strength after drying, recorded as M2. The retention rate of compressive strength = M2 / M1*100.

[0136] Samples were taken from the filling bodies of the underground filling area of ​​the coal mine with the age of 1d, 3d, and 7d, and the test blocks were processed into standard specimens of 50mm×100mm. The results of the single-side compressive strength test are shown in Table 1. The sample density is obtained from the sampling test of the filling body with the age of 7d.

[0137] The slump test is carried out using a 50×150×100mm CA mortar expansion tester, and the water seepage rate is mainly measured using a 185×200mm water seepage rate measuring bucket.

[0138] Table 1 Filling material properties of different embodiments and control examples

[0139]

[0140] According to the performance tested in Table 1, the slump of the heavy filling material slurry prepared by the present invention is not less than 180mm, and the water seepage rate is not more than 3.6%, which ensures good pipeline transportation performance in actual use. In addition, the 1d uniaxial compressive strength of the filling material of the present invention can reach more than 1.30MPa, and the 7d uniaxial compressive strength can reach more than 3.50MPa. At the same time, it has good water resistance, which can meet the requirements of most coal mine goaf filling mining for filling material strength; and the density of the filling body is not less than 1.69g / cm 3 , which is larger than coal, the filling body can be washed by heavy medium method, which can significantly improve the coal quality.

[0141] By comparing the test results of Example 1 with those of Examples 7-10, it can be seen that fibers of different lengths have a significant effect on the compressive strength, density and water permeability resistance retention rate of the filling body. This may be due to the different fiber lengths, which lead to different dispersions in the filling body, thereby affecting the compressive strength of the filling body. Specifically, fibers of suitable particle size can form an effective overlap with the modified iron tailings, thereby enhancing the bonding force of the matrix and improving the compressive strength and water resistance of the filling body. However, when the fiber length exceeds a certain limit, continuing to increase its length will have limited effect on improving compressive strength and water resistance. Therefore, choosing the right fiber length is crucial to optimizing the performance of the filling body.

[0142] By comparing Example 1 with Comparative Examples 1-3, we found that no activator was added to Comparative Example 1, while only calcium activator or sodium activator was added to Comparative Examples 2 and 3, respectively. The results show that the filling bodies of Comparative Examples 1-3 are significantly lower than those of Example 1 in terms of compressive strength, density and water resistance. This shows that the use of a combination of sodium activator and calcium activator can significantly improve the activity of calcined iron tailings, accelerate the dissolution of aluminosilicates, and promote the formation of hydration products, such as CSH gel and CASH gel, which significantly enhance the compressive strength of the material. At the same time, these hydration products, especially CSH gel, further enhance the water resistance and density of the material due to its excellent compactness and anti-penetration ability.

[0143] By comparing Example 1 with Comparative Examples 4-7, we found that Comparative Examples 4-5 only used fine particle size (d1<5mm) or coarse particle size (5≤d2<10mm), while the ratio of coarse particle size to fine particle size in Comparative Examples 6-7 exceeded the range of 1-3:5-8. The filling bodies of these comparative examples are significantly lower than those of Example 1 in terms of compressive strength, density and water resistance. This shows that the present invention optimizes the particle size combination of the filling material by mixing modified iron tailings of different particle sizes, effectively improves its rheological properties, and enhances the stability and fluidity of the filling body. In this method, the coarse-grained modified iron tailings construct a solid skeleton and provide the necessary support for the filling body; the fine-grained iron tailings penetrate and fill the gaps between the coarse particles, further improving the compactness of the filling body. This scientific ratio of coarse and fine particles promotes the uniform distribution of stress in the filling body, effectively avoids the problem of stress concentration, and thus enhances the overall stability of the filling body.

[0144] By comparing the results of Example 1 with Comparative Examples 8-10, it can be seen that when any one of the fibers, wollastonite or fly ash is omitted, the filling bodies of Comparative Examples 8-10 are significantly lower than those of Example 1 in terms of compressive strength, density and water resistance. This is mainly manifested in that the modified iron tailings play a cementing role in the filling body, and the early strength of the filling body is enhanced by forming hydration products such as hydrated calcium silicate (CSH) gel. The addition of fibers forms a mesh structure in the filling body, further improving the compressive strength, density and water resistance of the filling body. The high density characteristics of wollastonite help to improve the stability and density of the filling body, thereby enhancing the density and compressive strength of the filling body. Fly ash, due to its volcanic ash activity, can generate more hydration products such as CSH gel, which further improves the density, compressive strength and water resistance of the filling body. Therefore, the synergistic effect of fibers, wollastonite and fly ash is crucial to improving the comprehensive performance of the filling body.

[0145] The filling material of the present invention, which uses iron tailings, fly ash and wollastonite as main raw materials and is applied to coal mine filling and mining, can meet the normal production of coal mines. The slump of the filling material is not less than 180mm, and the water seepage rate is not more than 3.6%, which ensures good pipeline transportation performance in actual use. In addition, the 1d uniaxial compressive strength of the filling material of the present invention can reach more than 1.30MPa, and the 7d uniaxial compressive strength can reach more than 3.50MPa. At the same time, it has good water resistance, which can meet the requirements of most coal mine goaf filling and mining for the strength of filling materials; and the density of the filling body is not less than 1.69g / cm 3 , which is larger than coal, the filling body can be washed by heavy medium method, which can significantly improve the coal quality.

[0146] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine different embodiments or examples described in this specification and the features of different embodiments or examples, unless they are contradictory.

[0147] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Therefore, a feature defined as "first" or "second" may explicitly or implicitly include at least one of the features. In the description of this application, the meaning of "plurality" is two or more, unless otherwise clearly and specifically defined.

[0148] The above is only a specific implementation of the present application, but the protection scope of the present application is not limited thereto. Any technician familiar with the technical field can easily think of various changes or substitutions within the technical scope disclosed in the present application, which should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.

Claims

1. A heavy filling material, characterized in that: The filling material comprises the following components in parts by weight: 40-80 parts of modified iron tailings, 10-30 parts of fly ash, 10-20 parts of wollastonite, 5-10 parts of fiber, 1-8 parts of accelerating setting agent, 1-8 parts of suspending agent, 1-3 parts of water reducing agent, and 120-300 parts of water; The preparation method of modified iron tailings comprises the following steps: S1, crushing and drying 100 parts by weight of iron tailings, and uniformly mixing with 10-15 parts by weight of an activator, wherein the activator comprises a sodium activator and a calcium activator, wherein the sodium activator comprises at least one of sodium chloride, sodium sulfate, and sodium hydroxide; the calcium activator comprises at least one of calcium hydroxide, calcium oxide, calcium chloride, and gypsum, and the mass ratio of the sodium activator to the calcium activator is 1-3:5-10; S2, conveying the uniformly mixed material in step S1 to a rotary kiln for calcination, cooling, grinding, and passing through 10 mm and 5 mm sieves respectively to obtain a fine particle size of d1 < 5 mm and a coarse particle size of 5 ≤ d2 < 10 mm, and uniformly mixing the fine particle size and the coarse particle size according to a mass ratio of 1-3:5-8 to obtain a modified iron tailings.

2. The heavy filling material according to claim 1, characterized in that: The fibers include at least one of glass fibers, polypropylene fibers, polyester fibers, and basalt fibers, and the length of the fibers is 2-10 mm.

3. The heavy filling material according to claim 2, characterized in that: The length of the fibers is 4-8 mm.

4. The heavy filling material according to claim 1, characterized in that: The water reducer includes at least one of a naphthalene-based water reducer, a melamine-based water reducer or a polycarboxylic acid-based water reducer.

5. The heavy filling material according to claim 1, characterized in that: The accelerating setting agent includes at least one of sodium aluminate, sodium sulfate or sodium carbonate.

6. The heavy filling material according to claim 1, characterized in that: The suspending agent includes at least one of sodium carboxymethylcellulose, water-soluble polyvinyl alcohol or hydroxypropyl methylcellulose.

7. The heavy filling material according to claim 1, characterized in that In the step S2, the calcination temperature is 800-1400° C., and the calcination time is 2-5 hours.

8. A method for preparing the heavy filling material according to any one of claims 1 to 7, characterized in that: 1) Accurately weigh 40-80 parts of modified iron tailings, 10-30 parts of fly ash, 10-20 parts of wollastonite, 5-10 parts of fiber, 1-8 parts of accelerating setting agent, 1-8 parts of suspending agent, and 120-300 parts of water; 2) First, evenly mix the modified iron tailings, fly ash, wollastonite, fiber, accelerating setting agent and suspending agent, and then evenly mix with water to make a heavy filling material.

9. A method for preparing a heavy filling material according to claim 8, characterized in that: In step 2), the mixing temperature is 20-40° C. and the mixing time is 20-60 min.

10. Use of the heavy filling material according to any one of claims 1 to 7 in coal mine filling, characterized in that: The method comprises mixing the filling materials and then pumping the filling materials to the use site.

Citation Information

Patent Citations

  • Curing agent for filling iron tailings and preparation method thereof

    CN104045292A

  • Red-mud-based one-step-process geopolymer grouting material and preparation method thereof

    CN110028256A

  • Tailing-excited gelling filling material and preparation method thereof

    CN111848099A

  • Soft soil curing agent and preparation method thereof

    CN112159164A

  • Tailing solidification filling method, filling material, cementing agent and preparation method and preparation system thereof

    CN114772963A

Cited By

  • Deep sea tailing disposal method

    CN121892463A